ENGLISH TEACHERS’ KNOWLEDGE OF GENRE-BASED APPROACH: CONCEPT AND IMPLEMENTATION - Nabilah, Nadia (Premise: Journal of English Education and Applied Linguistics, 2023)
The Indonesian government places a high priority on revising and improving the curriculum to achieve the desired outcomes. Since 2004, the Genre-Based Approach (GBA) has been implemented as one of the approaches to teaching English. Although GBA has several benefits in English language teaching, there has been much concern that the outcomes still need to be achieved. This study investigated English teachers' understanding of the GBA concept and its implementation. Using a semi-structured interview, this study involved two high school English teachers in Aceh Tengah. Thematic analysis was used to analyze the data. It was found that English teachers' knowledge of the genre-based approach could be much higher and require further development and guidance. They need to show it to understand the general concept of GBA, text types, and basic GBA principles. Regarding GBA implementation, their lack of knowledge is shown by incomplete activities at certain cycle stages, difficulties in applying the stages, and inaccuracy in assessing students' achievement. Thus, it is suggested that teachers improve their knowledge of the approach practically and conceptually because the quality of the teaching processes is vital in achieving student learning success.